What do Street Children Need in the Shelter Home: A Narrative Review Study? - Fitriani, Lisa; Saidi, Sanisah; Susanti, Suryani Sulistiana (Journal of Language and Health, 2024)
Issues with street children, particularly in developing countries, seem to be alarming. Many countries reported increasing numbers. The aim of this research is to explore the experience support of street children in the shelter home, the question on how the experience of these street children when they are being placed in the shelter homes, and what the type of support is given to them? A comprehensive search of relevant databases from 2010 to August 2021 with critical key search focuses on the “street children's welfare" or "type support" and "experiences street children in various countries." Furthermore, the investigation of relevant databases yielded 313 hits, finally, 12 papers are suitable for the review with utilized the PRISMA review method in the process. This review has results support for street children, including theme; physiological support, phycological support, social support, and health care support. To conclude, street children have specific support needs; future program initiatives need to be developed that respond to street children's needs.